Organizational Ambidexterity for Indonesian Economic Development Research: Bibliometric Analysis - Suherlan, Arda Lintang Marthanda; Sinudarsono, Kevin; Wahyudi, Sugeng (LifeSciFi, 2024)
The study of organizational ambidexterity has been the focus of research attention in recent years. Yet, it is important to understand the evolution of research in this field and related trends. This research is expected to identify the gap between developments and trends in the world and developments and trends in Indonesia. In this study, a bibliometric analysis was conducted using 645 articles retrieved from the Scopus database. The results show that researches on organizational ambidexterity are on the rise. United State of America is the country with the most published articles with a percentage of 21% of total top 10 countries publications, while Indonesia has only 14 articles indexed by Scopus in this field. The most productive source or journal in the last five years is Sustainability (Switzerland). Researchers in this area have expanded their focus to new and different topics related to organizational ambidexterity, including sustainability, digital transformation, and entrepreneurial orientation. The findings of this paper can help academics and practitioners to better understand the research development trends in the field of organizational ambidexterity, as well as provide a comprehensive view for future research, especially in Indonesia.